Screening of laryngopharyngeal reflux disease in patients with gastroesophageal reflux disease symptoms in Hospital Universiti Sains - Apparau, Hema (2013)
Laryngopharyngeal reflux (LPR) has been recognized as an extraesophageal manifestation of gastro esophageal reflux disease (GERD). However, many questions still exist as how to diagnose this disease accurately and to identify patients with silent reflux. This study was conducted to determine the prevalence of LPR in patients with GERD symptoms in Hospital Universiti Sains Malaysia, Kubang Kerian. This is a cross sectional study involving 115 patients presenting to Gastroenterology clinic and Outpatient clinic in HUSM from December 2011 to June 2012. Participants were required to answer the Symptomatic GERD questionnaire and Reflux Symptom Index questionnaire. This was followed by laryngeal examination and documentation of Reflux Finding Score. The prevalence of LPR in patients with symptomatic GERD was 33.04%. The commonest symptom in RSI was ‘heartbum, chest pain, indigestion or stomach acid coming up’. The most commonest sign seen in RFS is ‘erythema’. There was significant correlation between RSI and RFS. LPR is present in patients with symptoms of GERD. RSI and RFS play an important role to identify patients with LPR and aid the clinician to deliver the appropriate treatment to them.